The Foundation of the Development of Science and Technology in the PAI Curriculum (Aqidah Akhlaq Curriculum Analysis) in Indonesia - Tatang Muh Nasir; Rika Siti Karimah; Gina Aria Sonia (Zona Education Indonesia, 2023)
The progress of a country is supported by the quality of human resources in it, advances in technology and knowledge are two things that greatly influence the development of the country. Future challenges in the form of the development of information technology, the convergence of science and technology, the advancement of creative and cultural industries, the influence and impact of technoscience, demand the implementation of a more comprehensive science and technology-based curriculum development. Aqidah as a belief system that contains the basic elements of belief, describes the source and nature of the existence of religion. While morals as an ethical system describes the direction and goals to be achieved by religion. This study aims to broaden readers' insight into the importance of improving the quality of human resources by improving education in Indonesia, one of which is through the development of a science and technology-based curriculum. The research method uses a descriptive qualitative approach. The results of the study explained that educational institutions, especially the school pathway, must be able to support and anticipate scientific and technological advances. Teaching materials or materials should be the result of contemporary scientific and technological developments, both related to the results of obtaining information, or how to obtain this information and use it for society. It takes the utilization, development and mastery of science and technology so that it has implications for the development of human resources.